Regarding certain stages of the development of quantum chemistry in Russia: Experience from the Ya.K. Syrkin Department of Physical Chemistry of the M.V. Lomonosov Institute of Fine Chemical Technologies - K. V. Bozhenko (Тонкие химические технологии, 2023)
Objectives. To analyze the history of the development of quantum chemistry and software for quantum chemical calculations in Russia at the Ya.K. Syrkin Department of Physical Chemistry of the M.V. Lomonosov Institute of Fine Chemical Technologies of RTU MIREA.Results. This work presents a historical overview of the development of quantum chemistry at the Ya.K. Syrkin Department of Physical Chemistry from Academician Ya.K. Syrkin to Professor V.R. Flid. It provides a summary of the work with the participation of the author in 1980s–1990s. Quantum-chemical models used to describe some of the intercalation reactions in a bond are considered in comparison with the well-known Woodward–Hoffman and Fukui approaches. The work outlines fundamentals of studies on the design of bifunctional compounds.Conclusions. The physical significance of the exchange interaction constant is given a visual meaning: it establishes the change in spin density on the metals forming complexes of the type in question when passing from isolated cations in the composition of the complexes. The work provides recommendations to synthetic chemists regarding the selection of components in the synthesis of magnetic sublattices of bifunctional materials. It also examines the high level of scientific research carried out at the Ya.K. Syrkin Department of Physical Chemistry and its relevance to the world science level.